Nasopharyngeal Meningococcal Carriage among Children and Adolescents in Turkey in 2018: An Unexpected High Serogroup X Carriage - Mahmut Can Kizil; Omer Kilic; Mehmet Ceyhan; Merve Iseri Nepesov; Adem Karbuz; Zafer Kurugol; Mustafa Hacimustafaoglu; Solmaz Celebi; Meltem Dinleyici; Kursat Bora Carman; Cihangul Bayhan; Yasemin Balliel; et al. (MDPI AG, 2021)
Meningococcal carriage studies and transmission modeling can predict IMD epidemiology and used to define invasive meningococcal disease (IMD) control strategies. In this multicenter study, we aimed to evaluate the prevalence of nasopharyngeal Neisseria meningitidis (Nm) carriage, serogroup distribution, and related risk factors in Turkey. Nasopharyngeal samples were collected from a total of 1267 children and adolescents and were tested with rt-PCR. Nm carriage was detected in 96 participants (7.5%, 95% CI 6.1-9.0), with the peak age at 13 years (12.5%). Regarding age groups, Nm carriage rate was 7% in the 0-5 age group, was 6.9%in the 6-10 age group, was 7.9% in the 11-14 age group, and was 9.3% in the 15-18 age group. There was no statistically significant difference between the groups (p > 0.05). The serogroup distribution was as follows: 25% MenX, 9.4% MenA, 9.4% MenB, 2.1% MenC, 3.1% MenW, 2.1% for MenY, and 48.9% for non-groupable. The Nm carriage rate was higher in children with previous upper respiratory tract infections and with a high number of household members, whereas it was lower in children with antibiotic use in the last month (p < 0.05 for all). In this study, MenX is the predominant carriage strain. The geographical distribution of Nm strains varies, but serogroup distribution in the same country might change in a matter of years. Adequate surveillance and/or a proper carriage study is paramount for accurate/dynamic serogroup distribution and the impact of the proposed vaccination.